proximity conflict's resolution and innovation networks of French biotechnology SMe's - Delphine Gallaud (European Regional Science Association (ERSA), 2005)
During the eighties, small Sme's of the so-called « Third Italy » obtain high performances. So Italian scholars ( Baganasco, 1977, Becattini, 1979, Brusco, 1982) underline some elements that remind the English districts studied by Marshall. These works open the way to a set of theories based on the same hypothesis of the importance of geographic proximity to innovate. Between them one can list innovative milieux (Aydalot, 1986, Camagni, 1991, Maillat, 1995), national and regional systems of innovation (Lundvall, 1992, Nelson, 1993, Edquist, 1997), local productive systems (Courlet, Pecqueur, 1989), technological districts (Saxenian, 1994) and clusters (Porter, 1998). But all these works have often postulated the real importance of geographic proximity to innovate, and the one of cooperation. Besides, the part of organizational proximity has been underestimated. So our problematic is to bring to the fore what are the factors which explain the coupling of geographic and organizational proximity. Biotechnology present important specificity, especially in terms of the importance of cooperation. But conflicts become very important too in this industry, besides they may increase because of the modification of property rights. We studied innovation networks of French biotechnology Sme's. As a first result, we brought to the fore that networks can use three kinds of global geographic proximity. Then we demonstrate that the kind of conflict's resolution explain the coupling of geographic and organizational proximity. Cooperative resolution is coupled with geographic proximity to solve conflicts and with organizational proximity (in the similarity logic). Avoiding resolution is coupled with no geographic proximity to solve conflicts (ICT are used to solve these conflicts), and with belonging kind of organizational proximity. At last, forcing resolution is coupled with belonging but with a little of geographic proximity to solve conflicts.
Keywords: 330